Understanding self-management related experience of patients with nasopharyngeal cancer: a review - Che Abdullah, Che Azunie; Saidi, Sanisah; Lee, Siew Pien (Elsevier Espana, 2021)
This review is conducted to understand the self-management experience among the patients throughout their cancer trajectory. Five databases were inputted systematic searches from February to April 2018. Several important themes emerged from the review, including their needs, facilitators, barriers, strategies, and provision of support towards self-management. The need for sufficient and appropriate information was the most severe concern among nasopharyngeal cancer patients. Understanding self-management from the patients’ perspectives may draw attention to specific concerns for self-management. However, the study of nasopharyngeal cancer patients is still under-researched. Therefore, exploratory research to understand their unique self-management experiences may help to design the care and support tailored to them to provide more holistic yet individualized care.